Experimental and Numerical Investigation of a Novel Spiral Micromixer with Sinusoidal Channel Walls - Bahrami, Dariush; Bayareh, Morteza (Chemical engineering & technology, 2022)
A novel spiral micromixer with sinusoidal channel walls was designed to enhance the mixing index in the low to intermediate Reynolds number range (1 < Re < 100). To analyze the fluid flow, a set of numerical simulations were performed using the finite‐difference method. The microchip was fabricated from polydimethylsiloxane, employing the soft‐lithography technique. The degree of mixing was increased by 99.11 % when using the proposed micromixer, compared to 59.44 % for a simple spiral micromixer. The introduced microchannel drastically reduced the mixing length, increasing the mixing index of a 0.5‐loop spiral‐sinusoidal microchannel compared to that of the simple spiral microchannel with 1.5 loops. The mixing index of the 3‐loop mixer was higher than that of the microchannel with 1.5 loops, and its pressure drop was increased. A novel spiral micromixer with sinusoidal channel walls, fabricated from polydimethylsiloxane, is proposed to enhance the mixing index in the low and intermediate Reynolds number ranges. A set of numerical simulations were performed, showing that the degree of mixing is increased by 99.11 %, while this value is 59.44 % for a simple spiral micromixer.